An atomistic simulation study of the crystallographic orientation relationships during the austenite to ferrite transformation in pure Fe. (26th October 2015) - Song, H; Hoyt, J J
Abstract: Molecular dynamics (MD) simulations on a model of pure Fe have been used in the investigation of solid-state nucleation of a body-centered-cubic (BCC) phase from a polycrystalline face-centered-cubic (FCC) matrix. A neighbor vector analysis (NVA) method has been introduced and it is shown how the NVA can be used to determine the misorientation of grain or interphase boundaries. In particular, the NVA was utilized to identify the orientation relationships (ORs) of several BCC nuclei and three special ORs were tested, namely the Kurdjumov-Sachs (KS), Nishiyama–Wassermann (NW) and Pitsch (P). From several quasi-2D simulations, it was found that all stable nuclei at grain boundaries formed at least one orientation relationship with the parent grains that was consistent with either the KS or NW relationship. Several initial MD simulation cells, which prohibited the formation of special ORs, were also examined and in these simulations no nucleation was observed after long run times. In addition, the orientation was detected in all mobile phase boundaries. Consistent with experimental findings, these observations demonstrate the importance of this high coherency atomic plane during both the nucleation and growth process. The nucleation and phase boundary characteristics identified here may provide important insights into the nucleation rate and grain orientation of more general solid state nucleation processes.